Moderating effects of gender in the relationships between daily stress, coping styles and hopelessness depression in adolescents - Rodríguez-Naranjo, María Carmen; Caño-González, Antonio (My University, 2016)
The hopelessness depression (HD) theory assumes a number of contributing factors to the development of hopelessness expectations and HD symptoms. Studies carried out to test HD theory have generally supported the prediction that a negative attributional style contributes to the development of hopelessness expectations and HD symptoms, although the evidence is less consistent for adolescents. Due to these inconsistent results, as well as the assumption advanced by HD theory that other factors aside from attributional style may contribute to the development of HD, in this study we examined the potential role of adolescents’ daily stress and coping styles as contributing factors to HD at these ages, and the effects of gender on these relationships. Seiffge-Krenke (1995) showed that stress in daily life plays a particularly relevant role during adolescence and described three coping styles used by adolescents to face daily stress: active and internal approach-oriented styles, which are considered functional and complementary, and avoidant style, considered dysfunctional. In this study, secondary students (N = 480; aged 13–17) completed the Hopelessness Scale (Beck, Weissman, Lester, & Trexler, 1974), the Hopelessness Depression Symptoms Questionnaire (Metalsky & Joiner, 1997), the Problem Questionnaire ((Seiffge-Krenke, 1995) and the Coping Across Situations Questionnaire (Seiffge-Krenke, 1995). To test the role of daily stress and coping styles in the prediction of hopelessness expectations and HD symptoms, two four-step hierarchical multiple regression analyses were conducted. In these analyses, gender was introduced first, daily stress was introduced second, the three coping styles were entered in a third step, and the moderating effects of gender on the associations of the predictor variables (daily stress and each coping style) with the criterion variables (hopelessness expectations or HD symptoms) were introduced in a fourth step. Results showed a moderating effect of gender on the relationship between daily stress and hopelessness expectations, which revealed a significant effect for boys despite the fact that girls experienced more daily stress than boys, thus suggesting an inoculation effect in girls. It was also found a gender-dependent role of coping styles in the prediction of HD symptoms, revealing a protective effect for the active style in girls and for the internal style in boys. This suggests that girls would benefit from being more action-prone and boys more reflection-prone in order to prevent HD. These findings indicate that programmes aimed to promote coping skills in adolescents would benefit from being gender-adapted.
Keywords: Depresión mental; Hopelessness; Depression; Adolescence; Coping styles; Daily stress